Evaluasi Risiko Konstruksi Pada Proyek Pembangunan Sadira Plaza Dan Tangram Hotel Pekanbaru - Hutasoit, Ardi Wiranata; Malik, Alfian; Iriana, Rian Trikomara (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Risk is an uncertain condition or event. A risk has a cause and if the risk occurs, there will be consequences so that an identifiable system must be established to reduce it to a minimum to the acceptable limit. The focus of this research is the risk of the construction of Sadira Plaza and Tangram Hotel Pekanbaru. The purpose of the research is to know the risk variables that affect the project and the design formula of risk management strategy. The research step with the distribution of questionnaires consisting of 9 variables or 50 risk indicators compiled with the dichotomy scale to the employees involved in the project is PT. Waskita Karya (Persero) Tbk as the contractor and PT.Target Optimal System Solutions as Construction Management Consultant obtained a total of 29 respondents with a valid questionnaire. Then the results of the questionnaire processed by using Cochran Q-Test, obtained 6 variables or 17 indicators that cause project risk. Furthermore, to analyze the fish bone diagram used to see the process of project implementation activities so as to know the root cause of the risk and make the formulation of the risk of development project of Sadira Plaza and Tangram Hotel Pekanbaru.Keywords: Fishbone Diagram, Risk, Dichotomy Scale, Cochran Q-Test